The effectiveness of service quality management practice in Kluang Mall to achieve customer satisfaction / Norshazliza Ramli - Ramli, Norshazliza (2009)
I choose the Service Quality Management as the topic of my study because the concept of service quality is the main attention in Kluang Mall as the new shopping mall in Kluang. Mall operation is increasingly recognizing that the environment significantly affects product evaluation, satisfaction and sales. Service is one of the products for Kluang Mall to get satisfaction from customers. In a shopping environment, consumers not only evaluate merchandise quality but also consider service quality. Customer will always look for quality where that is the main drivers of customers satisfaction. To achieve organization’s goal and to make customers satisfy at the same time, there are consistent theme in the field of service quality is the problem of identifying what comprise a service in order to determine the dimensions of the service which customers use to assess quality. There are different approaches to defining quality. Professor David Garvin categorized some of the definitions into what we called ‘five approaches’ to quality: 1) The transcendent approach, 2) The manufacturing approach, 3) The user-based approach, 4) The product-based approach 5) The value-based approach. Service quality has five identifiable parameters. This can be apply by Kluang Mall since it is new shopping mall and this parameters can either be designed into a new service or brought through training of the personnel which should also be an element in the design of the service. These dimensions are:1) Tangible, 2) Reliability, 3) Responsiveness, 4) Assurance, 5) Empathy. In this study, I will focus on a few issues in Kluang Mall related with Service Quality Management to the issues that contribute to the effectiveness of service quality in organization and compare with Kluang Mall Management practised.